LEXICAL-SEMANTIC ANALYSIS OF FRUIT PLANT NAMES IN THE BABURNAMA (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article examines the names of fruit trees and plants mentioned in the “Baburnama”, focusing on their lexical and semantic features. Special attention is given to the analysis of fruit names cultivated in Movarounnahr, Afghanistan, and India.